Immunomodulatory, Antioxidant, and Anti-Inflammatory Activities of Green Synthesized Copper Nanoparticles for Treatment of Chronic Toxoplasma gondii Infection - Abdullah D. Alanazi; Sultan F. Alnomasy (MDPI AG, 2023)
Background: Nowadays, interest in the use of nanotechnology for medical purposes is increasing. The current experimental investigation is planned for the green synthesis, characterization, and efficacy of copper nanoparticles (CLN) against chronic Toxoplasma gondii infection. Methods: Green synthesis of CNP was performed using the Lupinus arcticus extract via the precipitation method. The effects of CNP on tachyzoites, infectivity rate, parasites inside THP-1 cells, nitric oxide (NO) triggering, iNOS, and IFN-γ expression genes were evaluated. Following toxoplasmosis in BALB/c mice via the T. gondii ME49 strain, mice received CNP at 5 and 10 mg/kg/day alone and combined with pyrimethamine (PYM) at 5 mg/kg for two weeks. CNP's in vivo effects were evaluated by analyzing the load and size of cysts, oxidant/antioxidant enzymes, and bradyzoite surface antigen 1 (BAG1) expression gene levels. Results: CNP displayed a circular shape ranging from 10 to 85 nm. The IC50 value of CNP and PYM against tachyzoites was 37.2 and 25.7 µg/mL, respectively, whereas the CC50 value of CNP and pyrimethamine against THP-1 cells was 491.4 μg/mL and 269.5 μg/mL, respectively. The rate of infectivity and parasite load among THP-1 cells exposed to CNP was obviously reduced (p < 0.05). CNP at the doses of 5 and 10 mg/kg predominantly along with PYM evidently (p < 0.05) reduced the number and size of the T. gondii cysts in the infected mice. The levels of NO, iNOS, and IFN-γ genes were remarkably (p < 0.001) boosted compared with the cells without treatment. CNP at the doses of 10 and 20 mg/kg drastically (p < 0.05) reduced the oxidative stress markers in the infected mice, whereas CNP significantly elevated the level of antioxidant factors. CNP also revealed no toxicity in the liver and kidney at the tested doses in healthy mice. Conclusions: Our experimental study reported the beneficial effects of CNP principally along with existing chemical drugs against latent toxoplasmosis in mice, whereas the possible action mechanisms of CNP are controlling oxidative stress, refining antioxidant enzymes, and increasing the production of immunomodulatory cytokines with no toxicity to the function of vital organs. But, additional trials are required to confirm these results, as well as to clarify the accurate mechanisms and their toxicity.